RESEÑA de: Penas Ibáñez, Beatriz, López Sáenz, Mari Carmen (eds.). Interculturalism : between identity and diversity. Berna : Peter Lang, 2006 - Castillo Franco, Ignacio (Investigaciones Fenomenológicas, 2007)
_